Parental influence and self-efficacy for determining children's career interests in era society 5.0 - Mudhar Mudhar; Dimas Ardika Miftah Farid; Elia Firda Mufidah (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
Media information has provided a variety of knowledge about various kinds of careers. Parents are no longer the only information regarding career opportunities. They can determine the type of career independently based on the knowledge they get from the internet. This study aims to determine the influence of parents and self-efficacy on children's career interests in the 5.0 era. The method used is quantitative with correlation techniques. The subjects in this study involved 458 students from several universities in the city of Surabaya, using multistage random sampling. The data collection instrument used a scale of parental support, a scale of self-efficacy, and a scale of career interest. The analytical technique uses multiple regression to determine whether there is an influence between the variables studied. The results showed that there was no direct effect of parental support on children's career interests. Parental support can influence career interest through self-efficacy. Self-efficacy is also important for individuals to survive or give up on certain tasks or challenges. Various information obtained by students will make them more independent in determining attitudes and choices. Parents are only a motivator so that they are more confident in what they choose.